Development and Validation of a Stability-Indicating RP-HPLC Method for the Quantification of Daclatasvir in Tablet Formulation. - Himanshu, Himanshu; Verma, Suryakant; Jaishiv, Jaishiv; Sahu, Kshitiz; Sameeksha, Sameeksha; Mamgain, Anup Kumar (Journal of Neonatal Surgery, 2025)
A robust, stability-indicating reverse-phase high-performance liquid chromatography (RP-HPLC) method was developed and validated for the quantification of Daclatasvir in tablet formulations, employing separate methods for dissolution and assay determination. The dissolution method utilized an Inertsil C18 column (150 × 4.6 mm, 5 μm) with gradient elution comprising phosphate buffer (pH 2.5) and acetonitrile at a flow rate of 1.3 mL/min, with detection at 318 nm. Conversely, the assay method employed an isocratic elution using phosphate buffer (pH 7.0) and acetonitrile (60:40 v/v) on the same column at a flow rate of 1.5 mL/min. Both methods demonstrated excellent specificity, linearity (r² > 0.999), precision (%RSD < 2%), and accuracy within the acceptable recovery range of 98–102%. Forced degradation studies confirmed the methods’ capability to distinguish Daclatasvir from its degradation products, affirming their stability-indicating nature. The validated methods comply with ICH Q2 (R1) guidelines and are suitable for routine quality control and stability testing of Daclatasvir in pharmaceutical formulations, ensuring reliable assessment of both dissolution profiles and assay content....